Blocos para execução de alvenaria de vedação empregando garrafas pet: avaliação mecânica e termoacústica - Viegas, Leila Soares (2012)
Recycling and reuse of materials is the most evident solution regarding sustainable development. One relevant aspect to this development refers to the integration of engineering to devise ways that enable the reuse of materials considered as waste, but with great potential of applicability in the building industry itself, through the generation of appropriate technologies and products that can be an alternative to social housing. In this regard, this research aims to propose the use of PET bottles incorporating blocks for the implementation of fence masonry that provides thermal and acoustic protection, seeking its use in social housing. For the execution of the blocks, the PET bottles were inserted and centered in wooden forms easily made, which were subsequently filled with mortar. Three walls were executed in masonry with conventional ceramic brick and three walls with PET blocks for comparison of their performance concerning thermal, acoustic, and mechanical tests. Three types of mortar were used. The thermal test consisted in preparing panels 1.20 m of height and a width of 1.00 cm instrumented with five thermocouples on in both sides. The acoustic performance test was done in two ways, a simpler and other more complex using reverberating chamber. In both tests a sound source was placed in on one side and the sound pressure was measured before and after the wave crossed the walls. To obtain the mechanical performance the same panels were tested in a structural laboratory. The masonries with PET blocks showed in tests of thermal performance similar behavior to those built with conventional masonry. In the acoustic tests, masonry made with PET blocks performed better than the conventional ones. Concerning the mechanical performance, all three PET block walls reached greater compression strength than those with ceramic bricks, therefore the blocks with PET can be used in sealing walls. The manufacturing process of the PET blocks is simple and it could be applied by the poor organized communities to produce a construction product generating employment and income.